2017
DOI: 10.1007/s00216-017-0774-z
|View full text |Cite
|
Sign up to set email alerts
|

Determination of total phthalate in cosmetics using a simple three-phase sample preparation method

Abstract: A simple sample preparation method requiring minimal organic solvents is proposed for the determination of the total phthalate content in cosmetics by high-performance liquid chromatography-tandem mass spectrometry. The hydrolysis of phthalates and purification of interfering substances were performed in a three-phase system that included an upper n-hexane phase, a middle ethanol phase, and a lower aqueous alkali solution. This three-phase system utilized an incremental purification strategy. The apolar ingred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The results from a comparison of the proposed method to previously reported procedures for phthalate sum determination are shown in Table . During the hydrolysis process, this method and the other two developed by our group were much less time‐consuming than those for fatty food and urine because of the use of TBAB. Regarding clean‐up, either a large volume of organic solvent (80 mL C 2 H 5 OC 2 H 5 ) or a tedious SPE was applied; in the method for fatty food, a small volume of hexane was used because a pre‐extraction step was conducted before hydrolysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results from a comparison of the proposed method to previously reported procedures for phthalate sum determination are shown in Table . During the hydrolysis process, this method and the other two developed by our group were much less time‐consuming than those for fatty food and urine because of the use of TBAB. Regarding clean‐up, either a large volume of organic solvent (80 mL C 2 H 5 OC 2 H 5 ) or a tedious SPE was applied; in the method for fatty food, a small volume of hexane was used because a pre‐extraction step was conducted before hydrolysis.…”
Section: Resultsmentioning
confidence: 99%
“…Chromatographic separation was carried out at 35°C on a Shim‐pack XR‐ODS column (2.2 µm, 150×3 mm) from Shimadzu. The mobile phase consisted of water (A) and methanol (B) (both containing 0.1% formic acid) and was programmed as follows: linear gradient from 15 to 95% of methanol between 0 and 7.75 min and then keeping it constant for 2 min before being returned to the initial condition in 0.25 min . The column was re‐equilibrated for 5 min at the initial mobile phase composition, obtaining a total run‐time of 15 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A great number of immunoassays have been reported in the literature for the detection of different phthalates in food and in environmental matrices [48][49][50][51][52][53][54][55][56]. In cosmetics, the most used methods for the detection of phthalates are based on liquid chromatography [57,58]. Wei et al proposed an indirect competitive ELISA for the detection of DBP, and the technique was used to assess the presence of this target analyte in nail polish samples [59].…”
Section: Detection Of Prohibited and Restricted Cosmetic Ingredientsmentioning
confidence: 99%
“…13 Several analytical methods have been developed for the determination of PEs in cosmetic products. 9,[14][15][16][17][18][19][20][21][22][23][24][25][26][27] The most commonly used technique for the determination of PEs in perfumes is gas chromatography -mass spectrometry (GC-MS) e.g. 9,18,19,[28][29][30][31] Several studies have reported the presence PEs in perfumes in wide concentration ranges from sub ppm to high percentage.…”
mentioning
confidence: 99%